Anti-dsDNA antibodies and resident renal cells - Their putative roles in pathogenesis of renal lesions in lupus nephritis - Yung, Susan (Clinical immunology (Orlando, Fla.), 2017)
Copyright © 2016 Elsevier Inc. All rights reserved.